ANALISIS KEAKTIFAN PESERTA DIDIK MADRASAH ALIYAH REJANG LEBONG MELALUI PENGAMATAN VIDEO PEMBELAJARAN PADA MATERI TEKANAN HIDROSTATIS DAN HUKUM PASCAL MENGGUNAKAN TRANSCRIPT BASED LESSON ANALYSES - Anzani, Ali Via; Susanti, Nova; Dani, Rahma; Khairiyah, Julita (Universitas Jember, 2024)
This research was conducted to analyze student activities in Madrasah Aliyah Rejang Lebong. The data was then analyzed using the Transcript Based Lesson Analysis (TBLA) technique. This research carried out observations through learning videos which were documented on hydrostatic pressure and Pascal's law. The research method uses a mix method with an exploratory sequential approach where with this approach qualitative data is obtained first and then quantitative data can be obtained. The qualitative data that will be obtained will be in the form of conversation transcripts or conversational dialogue obtained using the TBLA technique. Then a more in-depth analysis of student activity can be carried out from the results of the student activity instrument obtained from the analysis of conversational dialogue which is adjusted to the category of student activity. The results of the research show that based on the student engagement instrument, the most prominent student activities are participating in carrying out their learning tasks, involved in problem solving and carrying out group discussions according to teacher instructions